2019
DOI: 10.19183/how.26.1.481
|View full text |Cite
|
Sign up to set email alerts
|

Language Assessment Practices and Beliefs: Implications for Language Assessment Literacy

Abstract: and an MA in the teaching of English as a second language from University of Illinois at Urbana-Champaign (USA). His interests include language assessment, curriculum design, and the professional development of English language teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
2
23
0
2
Order By: Relevance
“…When asked about why it was poor, most of them said that their past training did not include subject on statistics, and their current assessment context did not demand such practice. The poor ability in education measurement skills is similar to the study by F. Giraldo [20] that the participants in his study were also having difficulty related to educational measurement such as item construction and statistical calculation on validity and reliability. Similarly, based on a study by N. Sultana, [15] non-exact science teachers lacked the ability to analyze test items statistically.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…When asked about why it was poor, most of them said that their past training did not include subject on statistics, and their current assessment context did not demand such practice. The poor ability in education measurement skills is similar to the study by F. Giraldo [20] that the participants in his study were also having difficulty related to educational measurement such as item construction and statistical calculation on validity and reliability. Similarly, based on a study by N. Sultana, [15] non-exact science teachers lacked the ability to analyze test items statistically.…”
Section: Discussionsupporting
confidence: 79%
“…This study also suggested that teachers should attend more training about language assessment to equip them with the dynamic challenging of language assessment and with up-to-date assessment practices in order to improve the teachers' LAL. A study carried out by F. Giraldo [20] also recommended that the teachers in this study could take an advantage in participating in a professional development course that focus on not only theoretical but also practical aspects of language assessment. More importantly, program for developing teachers' LAL should also consider contextual factors as elements that can foster teachers' LAL.…”
Section: B Study On Teachers' Lalmentioning
confidence: 99%
“…Approaches to assessment like learning-oriented assessment or Assessment as Learning that highlight the involvement of the learner in the assessment process in order to improve learning, require the learners to be equipped with skills that would empower them to function competently in assessment, an important aspect of LAL in Inbar-Lourie's ( 2008) definition. While Wanatabe (2011) advocates explicit training of tertiary level language learners, a first step towards empowering learners in LAL could be to provide teachers with context-sensitive training measures focusing on fostering teachers' LAL, taking into account their "assessment life-worlds" (Scarino, 2013, p. 316), as well as considering their experience in assessment (Berry, Sheehan & Munro, 2019;Giraldo, 2019;Tsagari & Vogt, 2019). Empowering language teachers in this way would likely impact positively on learners' agency of assessment and their awareness of language assessment (Wanatabe, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…South America (Giraldo, 2019;Villa Larenas, 2018). Their potential contribution to bridging learning and assessment in high-stakes contexts is being researched (Baker & Riches, 2018;Xerri & Vella Briffa, 2018).…”
mentioning
confidence: 99%
“…I will start the discussion by first pointing out that resorting to the implementation of tests as the main way to assess students' speaking may not be significant if teachers fail to acknowledge that, regardless of its summative principles, testing may serve learners for formative purposes (López & Bernal; Muñoz et al as cited in Giraldo, 2019). Therefore, an alternative approach to speaking assessment practices should be implemented so that learners are encouraged to show their potential and confidence when delivering ideas, and not restrict their speaking assessment to summative practices (Huerta-Macias as cited in Brown & Hudson, 1998).…”
Section: Discussionmentioning
confidence: 99%